Assessing improvements in emergency department referrals to a hospital-based violence intervention program - Jayda Watkins; Na'il Scoggins; Brooke M. Cheaton; Mark Nimmer; Michael N. Levas; Shannon H. Baumer-Mouradian; Marlene D. Melzer-Lange (BMC, 2021)
Abstract Background Youth violence is a major public health concern in the United States. Hospital-based Violence Intervention Programs (HVIPs) are integral in connecting youth sustaining interpersonal violence-related injuries to medical, mental health, and social services. At our pediatric emergency department, our baseline referral rate to the established HVIP was 32.5%. From November 2018-2019, we aimed to increase the percent of eligible patients referred to our HVIP from 32.5 to 70% for patients aged 7-18 years who present to our Level 1 emergency department/trauma center with a violent injury. Methods For this quality improvement project, we recorded key aspects of the referral process, such as patient eligibility, who placed referrals, and when referrals were placed in relation to the ED admission. Key stakeholders were interviewed to identify specific interventions. Our key interventions were: 1. Educating providers on eligibility requirements. 2. Encouraging nurses to enter consults at the time of admission. 3. Publishing information about program referrals in the weekly nursing newsletter. 4. Updating social workers on eligibility requirements for the HVIP. We used PDSA cycles to inform our project. Our primary outcome measure was the number of eligible patients referred to our HVIP and measures were analyzed using statistical process control charts. Results The HVIP-eligible population had the following demographics: 31.1% female and a mean age 14.3 ± 2.7, 82.6% assaults and 17.4% gunshot wounds. From 11/2018 to 11/2019, there were 78 referrals to the HVIP, out of 167 eligible patients. The referral rate improved from 32.5% pre-interventions to 61.1% post-interventions, showing an 88% increase. Conclusion(s) We noted an increase in referrals to our HVIP following our interventions that centered on educating, advertising, and encouraging. Future studies will focus on analyzing other aspects of the enrollment process, such as obtaining patient consent.